The treatment process of a giant phyllodes tumor of the breast: a case report and review of the literature - Tong, Yujun; Liu, Siyu; Zhao, Lijuan; Zhang, Zhen; Hu, Haiyan; Jing, Yu; Liang, Tiantian (Frontiers in Oncology, 2024)
Giant phyllodes tumors are rare fibroepithelial tumors that are usually larger than 10 cm in diameter, have rapid tumor growth, and are easily recurrent. They are frequently accompanied by skin necrosis and infection, particularly in malignant phyllodes tumors. This case report presents a 50-year-old woman who presented to the hospital with a huge left breast mass that was ruptured and infected. The patient received anti-infective treatment and underwent mastectomy and skin grafting, which indicated a malignant phyllodes tumor. The tumor was completely excised after a local recurrence in the chest wall 6 months post-surgery. Unfortunately, one year later, the patient pass away due to multiple organ failure. Giant phyllodes tumor management presents challenges to the surgeon. This case is being presented to enhance understanding and treatment of phyllodes tumors, specifically giant malignant phyllodes tumors, with the aim of improving patients' quality of life.